Fast Diesel Aftertreatment Heat-Up Using CDA and an Electrical Heater Between 1.2 and 5.0 kW - Zavala, Bryan; McCarthy, James E.; Matheaus, Andrew; Sharp, Christopher (Frontiers in Mechanical Engineering, 2022)
Commercial vehicles require fast aftertreatment heat-up in order to move the SCR catalyst into the most efficient temperature range to meet upcoming NOX regulations while minimizing CO2. This paper is a follow-up paper using an electric heater upstream of a LO-SCR followed by a primary Aftertreatment system having an engine equipped with cylinder deactivation. The focus of this paper is to minimize the maximum power input to the e-heater without compromising tailpipe NOX and CO2. A system solution is demonstrated using a heavy-duty diesel engine with an end-of-life aged aftertreatment system targeted for 2027 emission levels using various levels of controls. The baseline layer of controls includes cylinder deactivation to raise the exhaust temperature more than 100° C in combination with elevated idle speed to increase the mass flowrate through the aftertreatment system. The engine load is adjusted to compensate for generating the electrical power on the engine. The combination of electrical heat, added load, cylinder deactivation and elevated idle speed allows the aftertreatment system to heat up in a small fraction of the time required by today’s systems. This work was quantified over the cold FTP, hot FTP, low load cycle (LLC) and the U.S. beverage cycle showing improved NOX and CO2 emissions. The improvement in NOX reduction and the CO2 savings over these cycles are highlighted.